Usefulness of Sonography in Enteric Fever of Paediatrics Age Group in India - B. B. Sharma; Shashi Sharma; Monu Dewan; Kumar Raju; . Pradhuman; . Gagandeep; Mansi Sheoran; Surabhi Lathwal; . Tushant (Current Overview on Disease and Health Research Vol. 2, 2022)
The present study was aimed at elucidating the usefulness of ultrasonography (USG) over the routine Widal test, Typhi dot IgM and hemoculture in the diagnosis of enteric fever. The study included 100 paediatric patients ranging in age from one to fifteen years. All of them had enteric fever, which was confirmed by typhi dot-IgM tests in the hospital’s paediatric department. The purpose of the USG was to assess the relevant findings. Blood samples for CBC, LFT and blood culture were taken on the same day as that of USG evaluation. USG evaluation of confirmed enteric fever cases revealed that 25% had gall bladder findings, 23% had hepato-splenomegaly, 11% had hepatomegaly, 1% had enlarged mesenteric lymph nodes (MLNs) and 3% had thickened caecum wall and ileocaecal junction. Many abnormalities associated to enteric fever can be diagnosed by USG, which is beneficial in initiating early therapy. Hemoculture and other tests may cause treatment to be delayed, resulting in a variety of problems.